Analisis Konstitusionalitas Batasan Kewenangan Presiden dalam Penetapan Peraturan Pemerintah Pengganti Undang-Undang - Prayitno, Cipto (Jurnal Konstitusi, 2020)
This paper is directed to notice about the limits of authority formation Government Regulation in Lieu of Act (PERPU) as outlined in Article 22 of the Indonesia Constitution 1945 as the excesses of the state that are considered critical and pushy or in legal terminology often referred to as matters of urgency to force. Nevertheless, the existence of Article 22 Indonesia Constitution 1945 as the legal basis of the authority of the President in the form Government Regulation in Lieu of Act (PERPU) not provide any legal certainty regarding presidential authority limits in the PERPU formation. The nature of subjectivity strengthened in the President becomes a problem and the pros and cons in any talks regarding the formation of this Government Regulation in Lieu of Act (PERPU) by using the methodology of normative legal research and the study of literature and used conseptional approach. On conclusion that there are three (3) main principal requirement Government Regulation in Lieu of Act (PERPU) their formation performed by the President based on the provisions of Article 22 of the 1945 Constitution and the law analisan results in this paper. These three things first is the limitation of time (when) a Government Regulation in Lieu of Act (PERPU) which by Maria Farida is limited (temporary) and limits the material (substance) were interpreted in the Constitutional Court Decision Number 138 / PUU-VII / 2009 as well as limits to the protection of the constitutional rights of the people.